The National Heroes in the Indonesian History Curriculum - Pramono, Suwito Eko; Ahmad, Tsabit Azinar; Utama, Nanda Julian; Atno, Atno; Kurniawan, Ganda Febri; Nurpratiwi, Hany; Plangsorn, Boonrat (Paramita: Historical Studies Journal, 2024)
Abstract: Indonesia has plenty of national heroes. In education, they have the potential as a medium for transmitting values and character education. From 1959 to 2023, the president awarded the title of hero to 206 people. This number will continue to increase every year. However, the contribution of learning about national heroes has not been studied in depth. Therefore, this paper aims to analyze how national heroes' mapping in history class and the heroes' position in the Indonesian History curriculum. This paper also examines the internalization of heroic values and obstacles encountered in historical learning. Data was collected on policies related to hero titles, curriculum documents, history textbooks, and learning cases about national heroes in Semarang City. The results showed that historical learning in the Indonesian curriculum accommodated the teaching of heroes. Some material addressed the role of the hero explicitly. However, not all heroes were conveyed in the lesson. Overproduction of heroes was counterproductive to students' recognition of the value of heroism. On the one hand, the role of local heroes had not been optimally reviewed. As a result, history learning was stuck on the term "learning about heroes." History learning has not entirely made students "learn from heroes" or "learn to be heroes." Abstrak: Indonesia memiliki banyak pahlawan nasional. Dalam dunia pendidikan, mereka memiliki potensi sebagai media transmisi nilai-nilai dan pendidikan karakter. Sejak tahun 1959 hingga 2023, presiden telah menganugerahkan gelar pahlawan kepada 206 orang. Jumlah tersebut akan terus bertambah setiap tahunnya. Namun, kontribusi pembelajaran tentang pahlawan nasional belum dikaji secara mendalam. Oleh karena itu, tulisan ini bertujuan untuk menganalisis bagaimana pemetaan pahlawan nasional dalam pelajaran sejarah dan kedudukan pahlawan dalam kurikulum Sejarah Indonesia. Tulisan ini juga mengkaji internalisasi nilai-nilai kepahlawanan dan kendala yang ditemui dalam pembelajaran sejarah. Data yang dikumpulkan berupa kebijakan terkait gelar pahlawan, dokumen kurikulum, buku teks sejarah, dan kasus pembelajaran tentang pahlawan nasional di Kota Semarang. Hasil penelitian menunjukkan bahwa pembelajaran sejarah di Indonesia dalam kurikulum (K13) dan Kurikulum Merdeka (KM) telah mengakomodir pengajaran tentang pahlawan. Beberapa materi membahas peran pahlawan secara eksplisit. Namun, tidak semua pahlawan tersampaikan dalam pembelajaran. Overproduksi pahlawan justru kontraproduktif terhadap pengenalan siswa terhadap nilai kepahlawanan. Di satu sisi, peran pahlawan lokal belum dikaji secara optimal. Akibatnya, pembelajaran sejarah hanya terpaku pada istilah "belajar tentang pahlawan". Pembelajaran sejarah belum sepenuhnya membuat siswa "belajar dari pahlawan" atau "belajar menjadi pahlawan".